Association between combined urinary phthalate metabolites exposure and grip strength among residents in Guangzhou, China - Jinbin Chen; Jie Shi; Guojun Xu; Guojun Xu; Wenru Feng; Jiayun Lv; Tongxing Shi; Qinqin Jiang; Qinqin Jiang (Frontiers in Public Health)
BackgroundExposure to environmental phthalate metabolites (mPAEs) has been suggested to potentially affect grip strength, either directly or indirectly. However, research on the impact of mPAEs mixtures on grip strength remains limited. This study aimed to investigate the independent and joint effects of co-exposure to multiple mPAEs on grip strength among residents of Guangzhou, China.MethodsData were collected from 972 participants, and urinary concentrations of nine mPAEs (mMP, mEP, miBP, mnBP, mCHP, mEOHP, mEHHP, mBzP, and mEHP) were measured. To assess these relationships, we conducted generalized linear regression models, Bayesian Kernel Machine Regression (BKMR), and Weighted Quantile Sum (WQS) regression analyses.ResultsThe Results showed that higher quartiles of mMP, miBP, mCHP, mEHHP, and mEHP were associated with decreased grip strength compared to the first quartile (Q1): mMP (Q4 vs. Q1: β = −1.44, 95% CI: −2.65 to −0.23, p = 0.019); miBP (Q2 vs. Q1: β = −1.78, 95% CI: −2.956 to −0.61, p = 0.003; Q3 vs. Q1: β = −1.39, 95% CI: −2.57 to −0.21, p = 0.002; Q4 vs. Q1: β = −1.23, 95% CI: −2.43 to 0.03, p = 0.045); mCHP (Q2 vs. Q1: β = −1.20, 95% CI: −2.38 to −0.03, p = 0.043); mEHHP (Q3 vs. Q1: β = −1.34, 95% CI: −2.53 to −0.16, p = 0.026); and mEHP (Q4 vs. Q1: β = −1.20, 95% CI: −2.39 to −0.01, p = 0.049). Restricted cubic spline (RCS) analysis indicated that grip strength gradually decreased as exposure concentrations of mMP (P-overall = 0.004) and miBP (P-overall = 0.037) increased, while the relationship between mEHP (P-overall = 0.022, P-nonlinear = 0.022) and grip strength exhibited an inverted U-shape. BKMR model analysis revealed a significant negative correlation between co-exposure to urinary mPAEs and grip strength, with mMP being the most significant contributor.ConclusionThis study demonstrates that exposure to mPAEs mixtures is associated with decreased grip strength, particularly influenced by mMP. These findings underscore the necessity for further investigation into the underlying mechanisms and potential modifiers of this association.